Perlindungan Hukum Atas Surat Keputusan Bupati Jayapura Perihal Tentang Pengosongan Rumah Dan Bangunan Milik Masyarakat (Studi Kasus Putusan Mahkamah Agung Nomor 326 K/TUN/2017) - Dody Surya Lubis (Jurnal Hukum dan Kemasyarakatan Al-Hikmah, 2020)
AbstractLand is a very basic human necessity. Humans live and carry out activities on land, so that almost all human activities, both direct and indirect, can be conveyed, always available land. Land as a natural resource given by God Almighty to the Indonesian people as a national wealth is a means in the activities of all people and has an important role for humans. The problem that will be examined in this writing is the legal protection of land rights to the community according to Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles, Description of the judge's decision regarding the jayapura regent's decree regarding the execution of a community land and building rights , due to the law of the decision of the Supreme Court No. 326 K / TUN / 2017 on the decision of the Regent of Jayapura regarding the emptying of houses and buildings that are subject to state administrative disputes. This research is descriptive with a normative juridical approach. "The normative juridical approach is to emphasize the science of law with a focus on secondary data, in the form of primary, secondary and tertiary legal materials". It was concluded that the protection of land that can be owned by the people according to the LoGA consists of Indonesian Nation Rights, which means that the Indonesian people's right to land has the meaning of the interests of the Indonesian people over the interests of individuals or groups. The Right to Control the State of the Land as a concept related to power has a number of intrinsic objectives as the bearers of the goals of all its citizens. The judge's decision on the Jayapura regent's decision letter in this case the object of the dispute was issued in the context of implementing the Defendant's policy to remove prostitution which had disturbed the community. The legal consequences of the decision of the Supreme Court Number 326 K / TUN / 2017 on the decision of the district head of the defendant to issue Object of Dispute I, Letter No. 413.4 / 0308 / SET March 2016 Subject: Vacancies for Houses and Buildings; the contents: Jayapura Regency Government will immediately make compensation payments and compensation to the legal owner; After payment is made, the legal owner of the land and building must immediately vacate the house / place of business / boarding / etc, no later than Thursday 9 March 2016. Keywords : Legal Protection, Decree, Vacancies, Houses, Buildings.Abstrak Tanah merupakan kebutuhan hidup manusia yang sangat mendasar. Manusia hidup dan melakukan aktivitas di atas tanah, sehingga dapat dikatakan hampir semua kegiatan hidup manusia, baik secara langsung maupun tidak langsung, selalu memerlukan tanah. Tanah sebagai sumber daya alam yang dikaruniakan Tuhan Yang Maha Esa kepada bangsa Indonesia sebagai kekayaan nasional merupakan sarana dalam menyelenggarakan seluruh aktivitas kehidupan rakyat dan mempunyai peranan yang penting bagi hidup manusia.Permasalahan yang akan dikaji dalam penulisan kali ini adalah perlindungan hukum hak atas tanah kepada masyarakat menurut Undang-Undang Nomor 5 Tahun 1960 tentang Peraturan Dasar Pokok-Pokok Agraria, Uraian keputusan hakim mengenai surat keputusan bupati jayapura tentang eksekusi atas suatu hak atas tanah dan bangunan masyarakat, akibat hukum putusan Mahkamah Agung Nomor 326 K/TUN/2017 terhadap keputusan bupati jayapura tentang pengosongan rumah dan bangunan yang menjadi objek sengketa tata usaha negara.Penelitian ini bersifat deskriptif dengan pendekatan yuridis normatif. “Pendekatan yuridis normatif yaitu menekankan pada ilmu hukum dengan menitik beratkan pada data sekunder, yang berupa bahan hukum primer, sekunder, dan tertier”.Disimpulkan bahwa perlindungan terhadap tanah yang bisa dimiliki masyarakat menurut UUPA terdiri atas Hak Bangsa Indonesia yang berarti hak bangsa Indonesia atas tanah mempunyai makna kepentingan bangsa Indonesia diatas kepentingan perorangan atau golongan. Hak Menguasai Negara Atas Tanah sebagai konsep yang berkaitan dengan kekuasaan memiliki sejumlah tujuan hakiki sebagai pengemban tujuan dari seluruh warga negaranya. Keputusan hakim atas surat keputusan bupati Jayapura dalam hal ini Objek sengketa diterbitkan dalam rangka pelaksanaan kebijakan Tergugat untuk menghapus prostitusi yang sudah meresahkan masyarakat. Akibat hukum putusan Mahkamah Agung Nomor 326  K/TUN/2017 terhadap keputusan bupati tergugat menerbitkan Objek Sengketa I, Surat No. 413.4/0308/SET Bulan Maret 2016 Perihal: Pengosongan Rumah Dan Bangunan; yang isinya: Pemerintah Kabupaten Jayapura akan segera melakukan pembayaran ganti rugi dan kompensasi kepada pemilik sah; Setelah dilakukan pembayaran, pemilik sah tanah dan bangunan wajib segera mengosongkan rumah/tempat usaha/kost/dll, paling lambat hari Kamis 9 Maret 2016.Kata Kunci  : Perlindungan Hukum, Surat Keputusan, Pengosongan, Rumah, Bangunan.